Charter and Revised Ordinances of the City of Eureka 251 (1905) - (:unkn) unknown (My University, 1878)
Penal Ordinances, Ordinance No. 55- Prohibiting the Carrying of Concealed Weapons, §§ 1-4: Prohibited the concealed carry of any pistol, dirk, or dangerous or deadly weapon. Violators guilty of a misdemeanor, punishable by fine not exceeding one hundred dollars, or imprisonment not exceeding ten days, or both.
Keywords: CARRY - CONCEALED